Information System Enterprise Architecture Design Academics at XYZ School Using TOGAF ADM - Widiadnyana, Putu; Andreyana, Putu Veda (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2023)
Information systems help all processes in an organization or school become easier and more efficient. However, implementing an academic information system in schools is not something that is easy to implement. Implementing information systems in schools requires careful and structured planning to produce a design that suits the needs, goals and objectives of the school. PlanningEnterprise Architecture can be done by using a framework to facilitate planning. TOGAF used to make plansEnterprise Architecture academic information system which includes business processes and academic activities at school. The design includes the TOGAF ADM phases with the stages of literature review, data collection,premilinary, architecture vision, business architecture, information system architecture, technology architecture, opportunities and solutions, and migration planning. The results of the design will obtain an information system that can connect several existing business processes at XYZ school. The results of this design are:blueprint which is used to simplify business processes in schools.